ANALISIS PERTUMBUHAN DAN HASIL PADI SAWAH (Oryza sativa L.) PADA SISTEM PERTANIAN KONVENSIONAL, TRANSISI ORGANIK, DAN ORGANIK - , EVAN MUNGGARA AGUNG ([Yogyakarta] : Universitas Gadjah Mada, 2013)
A research motivated by the trend of healthy living, back to nature, and practice of organic agriculture, and then organic rice farming havenât much discused about yield from conventional to organic transitional and organic crops. This study aims to observe and compare the efect of conventional, organic transitional, and organic crops. This research conducted in farmers fields on Tirtosari Village, Sawangan, Magelang regency, Central Java, in December 2011 until April 2012 used menthik wangi susu rice variety. Research compiled in a Completely Randomized Design (CRD) consists of 5 treatments. they were conventional, 3 levels organic transitional, and organic. every treatment was repeated 4 times for a total of 20 experimental units. Data were analyzed using analysis of variance (ANOVA) and continued by DMRT test with 95% of significance level. The results showed that the growth of rice planting in the conventional, organic transitional and organic crops were different. The convertion from conventional rice cultivation towards organic transitional causes a decrease in the growth at juvenil and return up to the next stage of transitional until become organic. On rice yield, a change in the conventional cultivation toward organic transitional has slightly increased and keep on rise until organic. Conventional planting method yields are 3.05 tons/ha, organic transitional 1 planting method yields are 3.06 tons/ha, organic transitional 2 planting method yields are 3.48 ton/ha, organic transitional 3 planting method yields are 3.59 ton/ha, and organic planting method yields are 4.86 tons/ha. On the conventional planting method have a low yield because a plant atacked by sundep pest. But not on organic transitional and organic.